Metabolism of thymine nucleotides synthesized via the 'de novo' mechanism in normal, megaloblastic and methotrexate-treated human cells and in a lymphoblastoid cell line. - Taheri, M R (1981)
Human bone-marrow cells and lymphocytes were incubated with [3H]deoxyuridine (dU) to study the metabolism of thymine nucleotides labelled via the thymidylate synthase (5,10-methylenetetrahydrofolate:dUMP C-methyltransferase, EC 2.1.1.45) step of the 'de novo' biosynthetic pathway. (1) Continuous labelling with [3H]dU was used to compare incorporation of label into DNA with the specific radioactivities of thymine nucleotides separated by paper chromatography. (2) Cells were also labelled with [3H]dU at 13 degrees C, and 'chased' in unlabelled medium at 37 degrees C in order to quantify the proportion of thymine nucleotides incorporated into DNA and the proportion degraded. Only 40% of labelled thymine nucleotides were incorporated into lymphocyte DNA during a 'chase', whereas 100% were incorporated by MOLT 4 cells (a lymphoblastoid cell line of thymic origin, Thy-ALL line). Unincorporated nucleotides were rapidly degraded in lymphocytes, but degradative activity was very low in MOLT 4 cells. The results described here reinforce our previous conclusions [Taheri, Wickremasinghe & Hoffbrand (1981) Biochem. J. 194, 451-461] that there is a single thymine nucleotide compartment in Thy-ALL cells, but at least two pools in lymphocytes and bone-marrow cells. This compartmentation of nucleotides in human cells is consistent with a model which proposes that deoxyribonucleotides are localized near replication forks by the activity of multienzyme complexes [Mathews, North & Reddy (1978) Adv. Enz. Regul. 17, 133-156]. Our results also suggest that thymine nucleotides derived by the 'de novo' mechanism may be more highly localized than those derived by salvage. In cells from patients with megaloblastic anaemia owing to deficiency of vitamin B12 or folate or in normal cells treated with methotrexate, there was a massive accumulation of labelled dUMP and decreased incorporation of label into DNA. There was no measurable incorporation of labelled deoxyuridine residues into DNA of megaloblastic cells, but deoxyuridine residues were detected in DNA of cells treated with methotrexate.